Semen analysis in fertile patients undergoing vasectomy: reference values and variations according to age, length of sexual abstinence, seasonality, smoking habits and caffeine intake - Sobreiro, Bernardo Passos; Lucon, Antonio Marmo; Pasqualotto, Fábio Firmbach; Hallak, Jorge; Athayde, Kelly Silveira; Arap, Sami (São Paulo Medical Journal, 2005)
CONTEXT AND OBJECTIVE: Recent studies have shown regional and population differences in semen characteristics. The objective was to establish reference values for semen analysis and to verify the effect that age, length of sexual abstinence, seasonality, smoking habits and coffee consumption have on fertile individuals’ semen characteristics. DESIGN AND SETTING: Prospective study in the Urology Division, Hospital das Clínicas, Universidade de São Paulo. METHODS: Between September 1999 and August 2002, 500 fertile men requesting a vasectomy for sterilization purposes were asked to provide a semen sample before the vasectomy. We evaluated the effects of age, sexual abstinence, seasonality, smoking and coffee consumption on semen characteristics. RESULTS: Compared with World Health Organization values, 87.2% of the patients presented sperm morphology below the normal level. A significant decline in semen volume, sperm motility and sperm morphology in patients over 45 years of age was observed. In patients with 5 days or more of abstinence, there was reduced sperm motility. The lowest values for sperm concentration, motility and morphology were observed in summer and the highest in winter. No differences in semen parameters relating to smoking were detected. Patients who drank six or more cups of coffee per day presented higher sperm motility. CONCLUSIONS: Our sample had a very low percentage of normal sperm morphology. Only sperm morphology showed a high abnormality rate. Differences in semen parameters with regard to age, length of sexual abstinence, seasonality and coffee consumption were identified. No differences relating to smoking were detected.